A convenient synthesis of core–shell ZSM-5@ZnO catalysts for methane co-aromatization with propane. (23rd August 2022) - Xu, Guohao; Gao, Xin; Luo, Tao; Duan, Yajie; Qian, Huan; Yu, Jisheng; Zhu, Xuedong
Abstract : The special reaction pathway of the shell (ZnO, metallic sites)–core (ZSM-5, acidic sites) and the relatively close proximity between ZnO and ZSM-5 were responsible for the excellent properties in methane co-aromatization with propane. Abstract : A novel core–shell ZSM-5@ZnO was successfully fabricated through a hydrothermal coating strategy, and the catalytic performance of ZSM-5@ZnO in the methane co-aromatization with propane (MCP) reaction was investigated using a physically-blended ZSM-5/ZnO catalyst as a comparison. Multi-techniques including XRD, ICP-AES, TEM, EDS, XPS, N2 adsorption, 27 Al NMR, IR and IG were employed to investigate the deactivation of the carbon deposition and the physicochemical properties of ZSM-5@ZnO. The results revealed that the introduction of methane into propane aromatization can promote the formation of Zn methyl species, further promoting the conversion of reactants and the formation of products. The MCP reaction at 550 °C revealed that ZSM-5@ZnO showed a higher methane and propane conversion and greater aromatic selectivity than those of the physically-blended ZSM-5/ZnO catalyst. The special reaction pathway of the shell (ZnO, metallic sites)–core (ZSM-5, acidic sites) and the relatively close proximity between ZnO and ZSM-5 were responsible for the excellent properties in MCP. Additionally, the formation of the micro–mesoporous property accelerated the mass-transfer rate and inhibited the formation of carbonaceous deposition, significantly enhancing the lifetime of the catalyst. Thanks to the novel core–shell structure of the ZSM-5@ZnO catalyst, it showed excellent properties in the MCP reaction.